ACTIVITY OF PERICARP EXTRACT OF MANGOSTEEN AGAINST ORAL STREPTOCOCCI: AKTIVITAS EKSTRAK PERICARP BUAH MANGGIS MELAWAN STREPTOCOCCI ORAL - Mustaqimah, Dewi Nurul; HW, Josh Erry (Dentika: Dental Journal, 2017)
The increasing prevalence of dental caries is still as a major world health problem. Caries is the direct result of acid production by cariogenic oral pathogens, especially Streptococcus mutans. New and better antimicrobial agents active against cariogenic bacteria with minimal side effects on the oral tissues are much needed, especially natural agents derived directly from plants. Phytochemical studies have shown that the extracts from various parts of mangosteen or Garciniamangostana Linn tree contain varieties of secondary metabolites such as prenylated and oxygenated xanthones, many of which have been found in vitro to have antimicrobial properties against oral pathogens. Several studies which examined the eficacy of herbal for human health have shown that xanthones from mangosteen have remarkable biological activities such as antioxidant, antimicrobial, anticancer etc, and had no cytotoxic effects on human gingival fibroblasts. Their results showed that among these xanthone derivatives obtain from pericarp extract of mangosteen, Î±-mangostin has the most potent antimicrobial activity against cariogenic Streptococcus mutans. It can be concluded that the strong antimicrobial activity of the pericarp extract of mangosteen is a good drug of choice that might be helpful in preventing the dental caries.